Effects of a traditional Chinese mind–body exercise, Baduanjin, on the physical and cognitive functions in the community of older adults with cognitive frailty: study protocol for a randomised controlled trial - Jing Tao; Rui Xia; Mingyue Wan; Huiying Lin; Pingting Qiu; Yu Ye; Jianquan He; Lianhua Yin; Lidian Chen; Guohua Zheng (BMJ Open)
Introduction Cognitive frailty (CF) is a clinical manifestation characterised by the simultaneous presence of both physical frailty and cognitive impairment among older adults without dementia and has become a new target for healthy ageing. Increasing evidence shows that regular Baduanjin (a traditional Chinese mind–body exercise) training is beneficial in improving physical function and cognitive ability in the older adults. The primary aim of this trial is to observe the effect of Baduanjin on physical and cognitive functions in older adults with CF.Methods and analysis In this prospective, outcome assessor-blind, two-arm randomised controlled trial, a total of 102 participants with CF will be recruited and randomly allocated (1:1) into the Baduanjin training or usual physical activity control group. The control group will receive health education for 30 min at least once a month. Based on health education, participants in the Baduanjin exercise group will receive a 24-week Baduanjin training with 60 min per session and 3 sessions per week, while those in the usual physical activity control group will maintain their original lifestyle. Primary outcomes (frailty index and global cognitive ability), body composition, grip force, balance, fatigue, specific cognitive domain, including memory, execution and visual spatial abilities, and life quality of secondary outcomes will be measured at baseline, and at 13 and 25 weeks after randomisation, while the structural and functional MRI will be measured at baseline and 25 weeks after randomisation. The mixed linear model will be conducted to observe the intervention effects.Ethics and dissemination The study has been approved by the ethics committee of the second people’s hospital of Fujian province (Approval no. 2018-KL015). Results will be submitted for publication in peer-reviewed journals and disseminated at scientific conferences.Trial registration number ChiCTR1800020341; Pre-results.